Observation of chiral bound states in the continuum in self-biased magneto-optical photonic crystals - Maohua Gong; Qiutong Zhen; Yujie Tang; Peng Hu; Qing-An Tu; Yan Meng; Peiheng Zhou; Zhen Gao (Proceedings of the National Academy of Sciences, 2026)
Chiral bound states in the continuum (BICs) are confined photonic modes with infinite quality factors and chiral response, offering significant potential for chiral optics. Although a novel type of spin-orbital-locking chiral BIC was recently predicted in magneto-optical (MO) photonic crystals (PhCs) that break time-reversal symmetry (TRS), its experimental realization has remained elusive. Here, we report an experimental observation of such chiral BICs in self-biased MO PhCs, which operate without external magnetic fields. Moreover, we experimentally demonstrate that the chirality and the surrounding near-circular polarization of these chiral BICs can be switched simply by reversing the remanent magnetization, without any structural changes. Unlike conventional chiral BICs that preserve TRS, these magnetically induced chiral BICs exhibit exceptional robustness against structural imperfections and perturbations. This work represents a significant advancement in topological photonics for chiral BICs, opening pathways toward robust chiral optical devices.